Influencia del almacenamiento en la concentración del hipoclorito de sodio utilizado como irrigante endodóntico, de los consultorios de especialistas en endodoncia, pertenecientes a la ciudad de Loja - Rosales Soto, Dayanna Lisseth (2022)
Sodium hypochlorite is a halogenated compound, its main function is organic matter dissolution. Nowadays, it is used as a first choice irrigant in endodontictherapy because of its properties. Nevertheless, it is a chlorinated solution, and the stability of its concentration is affected by certain factors. For this reason, this study researches the storage conditions that may be related to the loss of its concentration. This is an experimental, analytic, and descriptive study aimed to determine the influence of storage on the sodium hypochlorite concentration, used as an endodontic irrigant in the Specialist Offices in the City of Loja. Fifteen samples of NaOCl were collected from the Specialist Offices in the City of Loja. Later, these were sent to the "Center for Comprehensive Analytical Solutions CENTROCESAL Cía. Ltda.” laboratory, where the samples were analyzed according to the Ecuadorian Technical Standard (INEN), which through the iodometric method obtains the concentration of active chlorine, determining the real concentration of the samples. The result showed that the factors taken into consideration such as the place of storage, exposure to light, temperature, and type of container, do not have a higher level of significance in the mentioned loss. The storage place where sodium hypochlorite is located is not related to the loss of its concentration in the analyzed sample. So, it is important to consider the influence of other factors such as pH, expiration date, and commercial brand, among others, the same ones that can be considered in subsequent studies